THE ATTACKING METHODS INVOLVED IN CURRENT TREND ENVIRONMENT - Fitria, Rahma (Universitas Malikussaleh, 2021)
The use of Common Object Request Broker Architecture (CORBA) has become one of the answer to the requirement for interoperability among the rapidly increasing number of hardware and software products available nowadays. CORBA has been introduced as a mechanism in a distributed computing environment in order to overcome recent interoperability issue. This mechanism allows distributed objects to communicate with each other, whether operate on remote devices or local devices, written in different languages or platforms, or at different locations on a network. In this paper, the concept of CORBA application as a middleware is presented. In order to understand this concept, a simple program to handle auction sale. This system is developed using JAVA programming language. This application is implemented on Windows Operating System (OS) and its method is being invoked by a client from the other machine that also runs in Windows OS. Along with this, the benefits of CORBA and its limitation are discussed in this paper.Keywords”CORBA concept; client-server; benefits of Corba; Application example